ADHD and transitions to adult mental health services: a scoping review. Issue 6 (25th October 2013) - Swift, K. D.; Sayal, K.; Hollis, C.
Abstract There is increased awareness that attention deficit hyperactivity disorder (ADHD) continues into adulthood. Thus, health services are faced with a new challenge in providing a 'smooth' transition to adult services appropriate for young people with ADHD. This scoping review sought to identify the literature addressing transition for young people with ADHD to adult mental health services (AMHS). A scoping review, in which the search terms 'ADHD' and 'Transition' or 'Transfer' were entered into eight healthcare publication databases facilitated by NHS Evidence to identify both published and unpublished papers between 2000 and June 2013. Additional informal searches were also undertaken. Twenty‐three papers were selected for this review. This review confirms the lack of research explicitly tracking transition from Paediatrics/Child and Adolescent Mental Health Services (CAMHS) to AMHS for young people with ADHD. Only four papers directly studying transition for ADHD patients were identified. Three further studies surveyed clinician perspectives. Taken together, the studies address a number of issues in relation to transition, including the developmental course of ADHD symptoms, appropriate adult care, knowledge and communication, unmet need, comorbidities, environmental demands and medication cessation/dosage during the transition period. While literature surrounding transition exists, the scope of the evidence showing successful and unsuccessful transition activity from Paediatric and CAMHS to AMHS for young people with ADHD is limited. Future quality research in the form of audits, longitudinal tracking studies and service evaluations are required if we are truly to understand and identify what is needed and currently available for successful transition to an appropriate adult service for ADHD patients.